Teaching the Financial Markets Course - Scott, Robert Haney (Journal of Financial and Quantitative Analysis, 1976)
What we say here will surely have little effect on curriculum evolvement since changes in subject, content, and emphasis follow on the heels of significant improvements in theory or dramatic changes in the institutional setting, rather than on teacher preferences.